Seismostratigraphy of the Middle St. Lawrence Esturary: A Late Quaternary Glacial Marine to Estuarine Depositional/Erosional Record - Praeg, Dan; d’Anglejan, Bruno; Syvitski, James (Géographie physique et Quaternaire, 1992)
ABSTRACTA buried bedrock trough 350 m deep extends 100 km above Saguenay Fjord beneath the North Channel of the middle estuary. Four of five regional seismostratigraphic units are recognized in and adjacent to the trough; unit 1 (glacial ice-contact) and older sediments might also be present beneath the largely unpenetrated trough axis. Units 2 and 3 represent thick glacial marine sediments deposited in the >550 m deep waters of the Goldthwait Sea after glacial withdrawal ca. 13 ka BP: lower draped muds 10-20 m thick (unit 2) suggest deposition proximal to a retreating ice margin, while upper onlapping muds > 290 m thick (unit 3) record distal basin-filling; lateral transition to a coarse-grained proximal wedge 5*260 m thick (unit 2) is indicated by unit 3 reflectors rising and strengthening towards the Saguenay entrance, where a stable ice-margin ca. 13-11 ka BP supplied sediment to the lower and middle estuary. Unit 4 corresponds to lobes over 30 m thick on both sides of the upper North Channel, recording marginal input from glacial fluvio-deltaic sources. Unit 5 (estuarine sands, gravels and muds =£30 m thick) unconformably overlies glacial units. A smooth unconformity surface records erosion (at least 15 m, to axial depths >150m) by strong currents; irregular relief above depths of 25-50 m might relate to relative sea levels below present ca. 7-6 ka BP. Sand bedforms (apparently inactive) occur at the estuary floor, and possibly buried beneath estuarine muds; buried bedforms would imply an early Holocene genesis. Greatest thicknesses of estuarine mud coincide with adjacent fluvial discharges. Sandy/gravelly veneers form the estuary floor in most places. Mass displacement has disturbed units 3 and 5 along the northern, and locally southern, walls of the North Channel.